ANALISIS PENERAPAN ETIKA BISNIS ISLAM DAN URGENSINYA PADA UNIT-UNIT USAHA ORGANISASI KEMASYARAKATAN - Azwar, Azwar; Mulyawan, Andi Wawan; Usman, Abur Hamdi (Ekonomi Islam, 2024)
This research aims to analyze the application of Islamic business ethics in community organization business units and their urgency for the continuity of these business units, based on the perceptions of the actors and consumers, by taking case studies of business units within the DPP Wahdah Islamiyah in Makassar City. This research is field research using descriptive statistical analysis techniques. The research results show that Islamic business ethics, in the form of monotheism, justice, trust, and benevolence, have generally been applied to business units within the Wahdah Islamiyah DPP in Makassar City. Apart from that, the Islamic business ethics that have been implemented have great urgency in the management and service of business units, including as a factor that can bring blessings, create a work environment that is fair, inclusive, dignified, and in accordance with Islamic law, increase customer trust, and other parties so as to provide benefits to the company, improve, and provide excellent service to all parties because these ethics can support business management in accordance with company service guidelines, SOPs, and agreed rules. Keywords: Ethics, Business, Islam, Wahdah Islamiyah